An Exploration of Experiences and Academic Challenges of African Female Student at University of Zululand, South Africa (UNIZULU) - Tewari, Ankur (Journal of Education and Vocational Research, 2018)
Most African female students are weak in accounting. They feel that accounting is a male-dominated subject. Studies have shown that females consider accounting to be the masculine career. This study is an attempt to understand the academic challenges and experiences of African females at UNIZULU. With the aid of structured questionnaires, varied experiences and challenges of African female students at UNIZULU were captured and studied. Among the variety of experiences, few important ones are highlighted: academic support of lecturers, teaching and leadership style of lecturers, academic preparation of students, understanding of language and curriculum problems. In terms of challenges, students face problems related to language barriers, mathematical knowledge, time management, discipline and conduct, lack of female role model among others. The study suggested that UNIZULU should follow the gender-sensitive leadership and mentorship programs to improve female academic performance in the accounting modules.